Gonadal status and outcome of bariatric surgery in obese men. (12th December 2013) - Aarts, Edo; van Wageningen, Bas; Loves, Sandra; Janssen, Ignace; Berends, Frits; Sweep, Fred; de Boer, Hans
Summary Background Obesity‐related hypogonadotrophic hypogonadism (OrHH) occurs in over 40% of morbidly obese men. Obesity‐related hypogonadotrophic hypogonadism may reduce the beneficial effects of bariatric surgery. Objective To assess the impact of OrHH on the outcome of bariatric surgery in men. Patients and methods Observational study with measurement of serum gonadal hormones, and assessment of body composition, glucose, lipid and bone metabolism during the first year after bariatric surgery in 13 men with OrHH (free testosterone (free T) <225 pmol/l) and 11 age‐matched eugonadal morbidly obese men (free T > 225 pmol/l). Results Serum free T was inversely related to body weight (R = −0·65, P < 0·0001) and rose gradually after bariatric surgery, in eugonadal as well as in OrHH men, by 30 pmol/l for every 10 kg loss of weight. In three patients, serum free T remained within the hypogonadal range despite substantial weight loss. Gonadal hormone status prior to surgery did not affect the 1‐year outcome of surgery. Conclusion Obesity‐related hypogonadotrophic hypogonadism is a reversible condition in the majority of obese men. It does not reduce the efficacy of bariatric surgery. Preoperative weight‐adjusted normal values are recommended to avoid an incorrect diagnosis of hypogonadism in obese men.